Penerapan Asuhan Keperawatan Masalah Hipertensi Dan Perilaku Hidup Bersih Sehat Pada Warga Dusun Puarwase Kabupaten Manggarai - Fari Dewi; Bonavantura Nursi Nggarang; Helena Sarbunan (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Health problems in the form of infectious and non-communicable diseases originated from the lack of application of preventive and promotive efforts. Increased health problems such as acute respiratory infections and hypertension can be prevented by increasing promotive and preventive efforts for the community. The purpose of this service is to improve primary health services in the Puarwase Hamlet community in achieving optimal quality of life. This service was carried out on 211 families and 20 elderly people in Puarwase Hamlet, Manggarai Regency. Community service activities are directed at overcoming the problem of lack of clean hygiene behavior that results in acute respiratory infections and hypertension. The implementation of activities consists of assessment and health education, health examination, gymnastics and progressive muscle relaxation exercises in elderly hypertension. The impact of these community service activities is awareness of health problems by residents so that citizens have the awareness to overcome problems by empowering themselves through available resources such as health knowledge and skills and utilizing existing health facilities.